2018
DOI: 10.25289/ml.2018.7.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Facial Rejuvenating Effects of Mesotherapy Using a New Polycomponent Formulation

Abstract: Background and Objectives Facial rejuvenation via mesotherapy using a new polycomponent formulation was employed to improve skin texture. In this study, we evaluated the rejuvenating effects of a new polycomponent formulation through mesotherapy using a microneedle therapy system (MTS). Materials and Methods Twenty patients underwent a series of facial procedures, including three sessions performed at 2-week intervals and two sessions at 4-week intervals. Subsequently, 3 mL of new polycomponent formulation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…In most of the studies, serial micropuncture technique was used for injection. Others had used Nappage (picotage), depot and micro‐linear technique 1–34 . One study revealed significantly better improvement with Juvederm hydrate in biophysical measurements including anisotropy, hydration, and skin roughness along with high patients satisfaction with depot technique (mid‐to‐deep dermis injection) compared to picotage technique (superficial dermal injection) 15 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In most of the studies, serial micropuncture technique was used for injection. Others had used Nappage (picotage), depot and micro‐linear technique 1–34 . One study revealed significantly better improvement with Juvederm hydrate in biophysical measurements including anisotropy, hydration, and skin roughness along with high patients satisfaction with depot technique (mid‐to‐deep dermis injection) compared to picotage technique (superficial dermal injection) 15 .…”
Section: Resultsmentioning
confidence: 99%
“…10 Biophysical measurements and colorimetry showed improvement in both superficial and deep skin hydration, erythema, PH of skin, and sebum produc tion. [1][2][3][6][7][8][9]11,12,14 Histological and ultrasound evaluation confirmed clinicopathological and biophysical improvements was confirmed to continue up to 3 months by some studies. [1][2][3][6][7][8][9]11,12,14 In contrast, four studies revealed no significant improvement in clinical or histological features of skin with different compounds of mesococktail.…”
Section: Treatment Characteristics and Injection Techniquesmentioning
confidence: 94%
See 3 more Smart Citations